2020
DOI: 10.1002/chem.202000516
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Based Asymmetric Inverse Electron‐Demand Hetero‐Diels–Alder

Abstract: While artificial cyclases hold great promise in chemical synthesis, this work presents the first example of a DNA‐catalyzed inverse electron‐demand hetero‐Diels–Alder (IEDHDA) between dihydrofuran and various α,β‐unsaturated acyl imidazoles. The resulting fused bicyclic O,O‐acetals containing three contiguous stereogenic centers are obtained in high yields (up to 99 %) and excellent diastereo‐ (up to >99:1 dr) and enantioselectivities (up to 95 % ee) using a low catalyst loading. Most importantly, these result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“… 23 As for the design of the optimum DNA sequence, we took on board the observations made by Roelfes and Feringa who reported the strong influence of small self-complementary DNA sequences on both the enantioselectivity and the reaction rate. 15 They notably observed that 12-mers containing G-tracts lead to the highest levels of selectivity. With this in mind, we started our screening with 5′-GCCAGC S L/D GACCG-3′ ( ODN1 ), where S L/D corresponds to either ( l )-Ser ( S L ) or ( d )-Ser ( S D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 As for the design of the optimum DNA sequence, we took on board the observations made by Roelfes and Feringa who reported the strong influence of small self-complementary DNA sequences on both the enantioselectivity and the reaction rate. 15 They notably observed that 12-mers containing G-tracts lead to the highest levels of selectivity. With this in mind, we started our screening with 5′-GCCAGC S L/D GACCG-3′ ( ODN1 ), where S L/D corresponds to either ( l )-Ser ( S L ) or ( d )-Ser ( S D ).…”
Section: Resultsmentioning
confidence: 99%
“… 4 Indeed, since the pioneering work of Roelfes and Feringa, 5 who were the first to combine the chirality of the double helical structure of st-DNA with catalytically active metallic cofactors to catalyze a Diels–Alder cycloaddition, 6 the concept of DNA-based asymmetric catalysis (DAC) has been applied to an increasing number of enantioselective carbon–carbon and carbon–heteroatom bond-forming reactions, including Friedel–Crafts alkylations, 7 Michael additions, 8 syn -hydrations, 9 cyclopropanations, 10 fluorinations, 11 the hydrolytic kinetic resolution of epoxides, 12 the hydroamination of nitrostyrene, 13 the photocatalyzed [2 + 2] cycloadditions, 14 and more recently, the inverse electron-demand hetero-Diels–Alder. 15 Despite these achievements, the desire to tailor new DNA-based catalytic systems with improved efficiency, selectivity, and versatility remains an everlasting goal. We report here our efforts toward the development of a DNA/RNA hybrid catalytic system obtained through rational design and rounds of selection, which displays unprecedented levels of selectivity throughout the current DAC repertoire.…”
Section: Introductionmentioning
confidence: 99%
“…The enantioselective inverse‐electron‐demand hetero‐Diels‐Alder reaction catalyzed by supramolecular DNA hybrid catalysts was also reported [45] . The enantioselective cycloaddition reaction between azachalcones ( 10a – c , heterodiene) and dihydrofuran ( 11 , dienophile) is shown in Scheme 4.…”
Section: Dna‐based Hybrid Catalystsmentioning
confidence: 91%
“…As a solution, chelate ligands were bound to DNA via covalent or non-covalent interactions. In this way, peroxidase-like reactions and Zn II - and Ce IV -dependent site-specific RNA and DNA cleavage were established. Roelfes and Feringa pioneered the design of Cu II complexes that bind to double-stranded DNA for enantio­selective transformations such as Diels–Alder reactions, Michael additions, and Friedel–Crafts reactions. In recent times, also DNA G-quadruplexes were discovered for chiral catalysis, and a first example was reported in 2010 by Moses et al They showcased an enantio­selective Diels–Alder reaction by planar Cu II chelates, non-covalently stacked on a terminal G-quartet . Later, Wang and Li demonstrated Friedel–Crafts reactions, cyclopropanations, and other transformations.…”
Section: Introductionmentioning
confidence: 99%